The Use of the Jigsaw Technique on Students’ Reading Comprehension - Zulyanis, Fitri; Natasha, Harum (Indonesian Journal of Integrated English Language Teaching, 2024)
AbstractThis study was aimed at determining whether there is a significant effect on reading comprehension of class IX Junior High School Madrasah Tarbiyah Islamiyah (MTI) Agam Regency. This research s classified as quasi-experimental research. This study involved 53 students consisting of two groups, namely Class XI A as the experimental group and Class IX B as the control group. The experimental group was taught using the jigsaw technique, while the control group was taught using textbook-based techniques. Data were obtained using pre-test given to both groups before treatment and post-tests given after treatment. The pre-test and post-test data of both groups were analyzed using descriptive and inferential statistics. After the data was tested and declared homogeneous and normal, the hypothesis was tested using the Kolmogrov-Smirnov test. The results showed that there was a significant effect in reading comprehension between students who were taught using the jigsaw technique and students who were taught using textbook-based techniques.  The calculated significance value is 0.055 greater than 0.05 (sig value = 0.55> 0.05).  Therefore, this research hypothesis is accepted.  This means that there is significant effect in the reading comprehension of students who are taught using jigsaw technique as learning technique in class IX Junior High School Madrasah Tarbiyah Islamiyah (MTI)Bayur. Keywords: Jigsaw Technique, Reading, Reading Comprehension